2020
DOI: 10.1016/j.heliyon.2020.e05646
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the IFN-β-induced host signature informs repurposed drugs for COVID-19

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a causative agent for the outbreak of coronavirus disease 2019 (COVID-19). This global pandemic is now calling for efforts to develop more effective COVID-19 therapies. Here we use a host-directed approach, which focuses on cellular responses to diverse small-molecule treatments, to identify potentially effective drugs for COVID-19. This framework looks at the ability of compounds to elicit a similar transcriptional response to IFN-β, a type I int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 50 publications
3
13
0
1
Order By: Relevance
“…Recent studies have demonstrated the antiviral properties of narciclasine, an alkaloid found in various Amaryllidaceae species, and camptothecin, a topoisomerase inhibitor first isolated from the stem of Camptotheca acuminata (used in Chinese traditional medicine) against SARS-CoV-2 ( Huang C.-T. et al, 2020 ; Mamkulathil Devasia et al, 2021 ). However, importazole, an inhibitor of importin-β transport receptors, and other small molecules identified to reverse COVID-19-induced gene signatures need to be further explored because developing effective therapeutics is essential to control the COVID-19 pandemic ( Surnar et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the antiviral properties of narciclasine, an alkaloid found in various Amaryllidaceae species, and camptothecin, a topoisomerase inhibitor first isolated from the stem of Camptotheca acuminata (used in Chinese traditional medicine) against SARS-CoV-2 ( Huang C.-T. et al, 2020 ; Mamkulathil Devasia et al, 2021 ). However, importazole, an inhibitor of importin-β transport receptors, and other small molecules identified to reverse COVID-19-induced gene signatures need to be further explored because developing effective therapeutics is essential to control the COVID-19 pandemic ( Surnar et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Low risk of bias was detected in two studies [ 16 23 ]. Unclear bias was detected in four studies [ 24 25 26 27 ] because these studies explained the mechanism, pathogenesis, or the effect on the virus or in vitro experiment without any human trials.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, various studies demonstrated that SARS-COV2 proteins such as nsp1, 6, 13, and ORF6 target INF-β in order to evade the host innate immune mechanisms using ‘approaches’ such as inhibition of INF-β production, inhibition of its downstream signaling and development of resistance to interferon [ 11 , 12 ]. When compounds such as homoharringtonine, narciclasine, and anisomycin which are known to activate the transcription of INF-β were added in vitro to VeroE6 cells infected with SARS-COV2, it was found that they were able to inhibit viral replication thus providing an indirect evidence for the anti-inflammatory role of this type of interferon in COVID-19 [ 13 ].…”
Section: Sars-cov2 Infection: Overview Of the Inflammatory Responsementioning
confidence: 99%
“…Combined regimens with other antiviral drugs or with drugs able to enhance the IFN activities represents another path yet to be explored in more depth. Existing clinical data demonstrate the synergic effects of adding antivirals such as favipiravir to IFN-β, whereas other studies are focusing on compounds such as for example azithromycin which is able to enhance endogenous IFN signaling pathways and thus to contribute to an extra effect to the exogenous counterpart [ 13 , 40 ].…”
Section: Expert Opinionmentioning
confidence: 99%